STRATEGI PENGEMBANGAN INDUSTRI RUMAH TANGGA DI KOTA PEKANBARU (Studi Kasus Usaha Jamur Crispy Industri Pengolahan Jamur Tiram) - Muhammad Akbar Fatria; Jahrizal '; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Domestic industry not only plays a role in providing jobs, but also plays a role in economic empowerment. Manufacturing Enterprises crispy mushroom oyster mushroom is engaged in the cultivation of oyster mushrooms and post-harvest processing. This study aims to determine the development strategy of industry in the city of Pekanbaru (business case studies Manufacturing crispy mushroom oyster mushroom). As this study used secondary data and primary data obtained from the Central Statistics Agency Pekanbaru City and obtained directly from the respondent businesses crispy mushroom Oyster Mushroom Processing Industry in the city of Pekanbaru. Population businessman crispy mushrooms Oyster Mushroom Processing Industry in Pekanbaru city has 9 business units. The analytical method used in this research is descriptive method by using SWOT analysis.Based on the results of SWOT analysis, shows that the effort mushroom crispy oyster mushrooms Processing Industry in the city of Pekanbaru have a strategy in developing the business, as well as in dealing with problems in the internal and external environment of the industry. Where this strategy is in quadrant 1. The strategy should diretapkan in these conditions is to support aggressive growth policy. This aggressive strategy to focus more on strategy SO (strenght-opportunities), by using force to take advantage of existing opportunities. The strategies SO (strenght-opportunities) are: (1) Increasing the expertise of human resources, (2) Improved Promotional Activities, (3) Product DiversificationKeywords :SWOT Analysis,Strategy,Crispy Mushrooms